Indicadores de sustentabilidade do solo em sistemas alternativos ao uso do fogo, baseados nos princípios da agroecologia, desenvolvidos por agricultores familiares na região da Rodovia Transamazônica - Oeste do Pará - SERRA, Anderson Borges (Universidade Federal do Pará, 2021)
Agriculture is a human activity essential for society, for all level of development. The big question today is how to keep it productive without dramatically affecting the various terrestrial ecosystems. Soil can be considered the basis for sustaining agricultural systems. Thus, losses in properties, which reduce the ability to sustain plant growth or that involve risks, negative impact of great significance to rural communities, with repercussions on the urban environment. Among the factors that make the land productive and unsustainable in environmental terms, is the use of fire as a way of cleaning the areas for implementation of agricultural crops. The fire, one of the oldest technologies incorporated into production systems, is used to this day, for easy cleaning of the area and make the nutrients readily available to the vegetation stage of cultivation, through the ashes. Nevertheless, it is major problem due to its negative effects. It was within this context that a group of farmers under the articulation of a regional organization, the Foundation Live, Produce and Preserve, decided to begin an experiment aimed at testing practical implementation of agricultural system without using fire, intending to maintain soil fertility . These alternative systems, so-called "Roca Without Burning," are characterized by the implementation of agroforestry systems based on the principles of agroecology. This study seeks to understand how these "systems of farm without burning, can influence the maintenance of sustainability of the soil, its ability to perpetually harvest and renewal of biomass systems. For both, were studied as indicators of sustainability of some attributes related to soil organic matter and soil microbial biomass, because there is a growing perception consider them indicators of sustainability. Soil samples were made in the municipalities of Medicilândia Uruará and at the end of the dry season, January 2005, at depths 0-5, 5-10, 10-20 and 20-30. The systems were chosen to be monitored as the main component of cocoa to be an economically important crop in the Tran-region. The results showed that the stock of litter in soil microbial biomass carbon, soil organic carbon and total nitrogen, basal respiration and derived indices (ratio organic carbon / total nitrogen, compared microbial carbon / organic carbon and metabolic quotient pain indicators studied are not sensitive to changes in soil management system. The data support the idea that the agroecosystems of "slash without burning," are capable of storing large amounts of organic material, with a tendency for carbon storage and maintenance of fertility soil, making it therefore a promising agricultural practice for the development of family farming on a sustainable basis